PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWAKELAS X.1SMANEGERI 9 PEKANBARU - Ihsany, Saratul Ihsany; Hutapea, Nahor Murani Hutapea Murani; Roza, Yenita Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research aims by the students’math achievement at class X.1 SMAN 9 pekanbaru. This research is aims to increase learning process and students’ math achievement at class X.1 SMAN 9 pekanbaru in Three-Dimensional, through the implentation cooperative learning model of structural Think Pair Square. The subject are 32 students from class X.1 SMAN 9 pekanbaru consist of 10 male and 22 famale students with the heterogenous level. Technique of collecting the data use observation and math achievement test. The finding of the study indicated that there is improve in students’ achievement that can be seen from the percentage of students’ achive passing gradewith average is about 40,63%. The percentage of the score increase about 50,00% at the first test and about 65,63% at the second test. Based on the finding can be concluded that the implentation of cooperative learning model of structural approach Think Pair Square to improve students’ math achievement at class X.1 SMAN 9 pekanbaru of Three-Dimensional on main topic of second semester 2013/2014. KeyWord :Students’ math Achievement, Cooperative Learning Model Structural Approach of Think Pair Square, Classroom Action Research.